Exosomes Released from Tumor-Associated Macrophages Transfer miRNAs That Induce a Treg/Th17 Cell Imbalance in Epithelial Ovarian Cancer - Zhou, Jieru; Li, Xiaoduan; Wu, Xiaoli; Zhang, Ting; Zhu, Qinyi; Wang, Xinjing; Wang, Husheng; Wang, Kai; Lin, Yingying; Wang, Xipeng (Cancer immunology research, 2018)
The immune microenvironment is crucial for epithelial ovarian cancer (EOC) progression and consists of tumor-associated macrophages (TAM) and T lymphocytes, such as regulatory T cells (Treg) and T helper 17 (Th17) cells. In this study, the Treg/Th17 ratio was significantly higher in EOC and in metastatic peritoneal tissues than in benign ovarian tumors and benign peritoneum. The Treg/Th17 ratio was associated with histologic grade and was an independent prognostic factor for overall survival of EOC patients. On the basis of microarray analysis of exosomes derived from TAMs, we identified miRNAs enriched in the exosomes, including miR-29a-3p and miR-21-5p. When the two miRNA mimics were transfected into CD4 T cells, they directly suppressed STAT3 and regulated Treg/Th17 cells, inducing an imbalance, and they had a synergistic effect on STAT3 inhibition. Taken together, these results indicate that exosomes mediate the interaction between TAMs and T cells, generating an immune-suppressive microenvironment that facilitates EOC progression and metastasis. These findings suggest that targeting these exosomes or their associated miRNAs might pave the way for the development of novel treatments for EOC.